Hubungan Etika Digital dengan Kecenderungan Perilaku Cyberbullying Siswa di MTsS Sungai Rambah - Risya Aulia Nita Putri; Fenny Ayu Monia (YASIN, 2026)
Although cyberbullying behavior among adolescents is increasing alongside the widespread use of digital media, studies specifically analyzing its relationship with digital ethics among madrasah students remain limited. This study aims to analyze the relationship between digital ethics and students’ tendency to engage in cyberbullying at MTsS Sungai Rambah. This study employed a quantitative approach with a correlational design and involved 97 students selected using total sampling. Data were collected using a Likert-scale questionnaire that met the validity and reliability criteria and were subsequently analyzed using descriptive statistics, normality testing, linearity testing, and Pearson Product–Moment correlation analysis with the assistance of IBM SPSS Statistics. The results showed a significant negative relationship between digital ethics and the tendency to engage in cyberbullying (r = −0.690; p < 0.001), indicating that the higher the students’ digital ethics, the lower their tendency to engage in cyberbullying. These findings strengthen the development of the concepts of digital ethics and digital citizenship in the context of Islamic education and affirm the importance of internalizing moral values in shaping students’ digital behavior. This study concludes that strengthening digital ethics is an important strategy for preventing cyberbullying in madrasah environments. The practical implications require schools, teachers, and parents to integrate digital ethics education into learning, character development, and digital literacy programs, while also opening opportunities for further research involving broader populations and more diverse variables.